Supplementary file 2_Clinical efficacy and metabolomics profiling of dachaihu decoction for patients with septic liver injury: a randomized controlled trial.doc - Zhen Yang (107412) (2025)
Background Septic liver injury (SLI) is a life-threatening complication of sepsis with limited therapeutic options. The clinical efficacy and safety of Dachaihu Decoction (DCHD) in SLI remain to be elucidated. Methods and Design A prospective, single-center, single-blind, randomized, and placebo-controlled clinical trial was conducted. Patients in the DCHD group received DCHD twice a day for five consecutive days on the basis of sepsis bundle, while patients in the placebo group were administered a placebo at the same dosage. Primary outcomes included: (1) liver function indices: alanine transaminase (ALT), aspartate transaminase (AST) and total bilirubin (TBil); (2) Sequential Organ Failure Assessment (SOFA) and Acute Physiology and Chronic Health Evaluation II (APACHE II) scores; (3) 28-day all-cause mortality. Secondary outcomes included the evaluation of several clinical parameters: (1) infection indicators; (2) coagulation indicators; (3) gastrointestinal function indicator; (4) metabolic and respiratory function indicators. Subsequently, we employed Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) to characterize the serum metabolomics profiling of two groups of patients. Results DCHD significantly reduced TBil (−22.50 (interquartile range, IQR, −37.20, −8.10) vs. −3.30 (−17.16, 12.40), p < 0.001), SOFA score (−2.46 ± 2.84 vs. −1.11 ± 2.71, p = 0.047), APACHE II score (−5 (IQR, −5, −2) vs. −2 (−5, 2), p = 0.034), and Oxygenation Index (OI) (29.71 ± 74.76 vs. −15.16 ± 108.51, p = 0.048). However, no statistically significant difference in 28-day all-cause mortality was found between the DCHD and the placebo groups (7 (20.0%) vs. 9 (25.7%), p = 0.569). Additionally, our study demonstrates that DCHD ameliorates systemic infection, coagulation function, gastrointestinal function, and metabolic function in patients to a certain extent, and no severe side effects were reported. Metabolomics analysis reveals that Wogonin, Wogonoside, Cholic acid, and Glycocholic acid are representative differential metabolites, and bile acid metabolism may be the core metabolic pathway. Conclusion As an adjunctive therapy, DCHD demonstrates safety and efficacy in the treatment of SLI, particularly cholestatic hepatic dysfunction, which may be intimately linked to its modulation of bile acid metabolism. Clinical Trial Registration http://itmctr.ccebtcm.org.cn, identifier ITMCTR2025000095.